Determinants of the relative abundance of rodents in landscapes dominated by Eucalyptus plantations. (4th May 2022) - Teixeira, Daniela; Magalhães, Ana; Ares-Pereira, Guilherme; Lima, Cátia; Castro, Guilherme; Camarinha, Cláudia; Fonseca, Carlos; Rosalino, Luís Miguel
Abstract: Forestry plantations have increased considerably over recent decades to fulfil human demand for wood, pulp and paper. Eucalyptus globulus Labill is one of the most abundant plantation species, particularly in Europe, where its largest presence is in Portugal. Furthermore, plantations in Mediterranean areas, such as Portugal, frequently suffer from forest fires, and thus it is crucial to understand their impacts on vertebrates. This is especially relevant for some species, like small mammals, that use landscapes at smaller scales for which even small changes in forest cover may have a profound effect. In this study, we evaluate the effects of several environmental, disturbance and habitat drivers on the relative abundance of rodents (Muridae) in Eucalyptus plantations in central Portugal. Specimen capture took place across two seasons and at eight study sites representing six different stages of Eucalyptus plantations and two native forests from 2019 to 2020. Using a structural equation modelling approach, we show that the relative abundance of rodents was promoted by recent wildfire events and was higher in areas where carnivores and wild boar were more abundant. By contrast, abundant deer and increased percentages of herbaceous or litter cover and bare soil limited the abundance of rodents. We did not detect a significant relationship between Eucalyptus plantations and the relative abundance of rodents. The presence of other species, either by direct contact (carnivores) or by inducing habitat changes (ungulates), and vegetation structure, likely linked to plantation management or fire regime, are the more important factors dictating the population dynamics of rodents across plantation forests in central Portugal.